2018
DOI: 10.1002/jclp.22560
|View full text |Cite
|
Sign up to set email alerts
|

National norms for the expanded version of the inventory of depression and anxiety symptoms (IDAS‐II)

Abstract: The present study provides information on the distribution of specific internalizing symptoms in a large national sample, as well as on how these symptoms are related to demographic characteristics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
35
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(46 citation statements)
references
References 40 publications
10
35
1
Order By: Relevance
“…As expected, levels of depression were somewhat elevated in the present sample (M = 39.9, S.D. = 12.8), which corresponds to the 60th percentile in U.S. normative data; Nelson et al (2018).…”
Section: Acknowledgementssupporting
confidence: 80%
“…As expected, levels of depression were somewhat elevated in the present sample (M = 39.9, S.D. = 12.8), which corresponds to the 60th percentile in U.S. normative data; Nelson et al (2018).…”
Section: Acknowledgementssupporting
confidence: 80%
“…MTurk has been shown to provide data that have sound psychometric properties (Paolacci & Chandler, 2014), and demographic surveys demonstrate that MTurk workers are very similar to the national populations from which they are drawn (Paolacci, Chandler, & Ipeirotis, 2010). In addition, MTurk has been used in prior clinical and measure development studies (Shapiro, Chandler, & Mueller, 2013), as well as to define national norms of a common clinical measure (i.e., inventory of depression and anxiety symptoms; Nelson, O'Hara, & Watson, 2018). Researchers have demonstrated that data obtained by MTurk workers are similar to data collected from college undergraduates or community samples derived from college towns in domains such as political orientation (Berinsky, Huber, & Lenz, 2012), personality characteristics (Buhrmester, Kwang, & Gosling, 2011), and basic biases in decision making (Paolacci et al, 2010).…”
Section: Methodsmentioning
confidence: 99%
“…The three MDD risk factors were not associated with each other (ps>.05). Participants reported an average IDAS General Depression score of 32.92 (SD=8.86), which corresponds to the 44 th percentile in a national norming sample (Nelson et al, 2018). Depression severity was greater in individuals with a history of MDD (M=37.40, SD=9.44) compared to healthy controls (M=28.28, SD=5.14), t(45.12)=4.63, p<.001, d=1.22, but did not differ between participants with and without a family history of MDD,t(40.75)=1.39,p=.173,d=.39,and was unrelated to the RewP,t(57)=.91,p=.367.…”
Section: Depression Risk Factors and Esmmentioning
confidence: 99%